Clinical characteristics of stable angina patients and their treatment strategies in real-world clinical practice. A Russian PERSPECTIVE Study (Part I) - M. G. Bubnova; D. M. Aronov; R. G. Oganov; O. G. Rudomanov; A. S. Putylina (Кардиоваскулярная терапия и профилактика)
Aim. In a clinical and epidemiological study PERSPECTIVE, to investigate the secondary prevention implementation among stable angina patients in real-world clinical practice, and to evaluate compliance to Russian and international clinical guidelines on stable angina management. Material and methods. The study involved general practitioners and cardiologists (n=277). In the first part of the PERSPECTIVE Study, the data from out-patient medical histories (2768 patients with verified diagnosis of stable angina, SA) were analysed. Results. In SA patients, the prevalence of coronary risk factors (RFs) was high. The mean levels of blood pressure, blood lipids and lipoproteins, body mass index, and heart rate were substantially higher than the recommended target levels. At the same time, some positive changes in the clinical course of SA were observed, such as reduced incidence of angina attacks, decreased number of administered nitroglycerine tablets, and increased prevalence of Functional Class I-II SA. The qualitative changes in prescribed medications, including antianginal, anti-aggregant, and lipid-lowering agents, were also observed. Conclusion. The results obtained point to the need for further improvement of SA management in real-world clinical practice and for optimization of pharmaceutical therapy, in accordance with modern Russian and international clinical guidelines.